The Impact of Cultural Norms on Tax Compliance: A Global Empirical Analysis - I Gusti Agung Prama yoga; I Ketut Yadnyana; I Gusti Ayu Made Asri Dwija Putri; I Dewa Nyoman Badera (Universitas Warmadewa, 2025)
This article presents a systematic review of international literature examining the relationship between culture and tax compliance from 2015 to 2025. By adopting a cultural economics approach, the study aims to understand how social norms, collective values, cultural identity, and psychosocial factors shape tax compliance behavior. The search and selection process followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) and the Joanna Briggs Institute (JBI) approach. This process yielded 40 empirical, peer-reviewed articles that met the inclusion criteria. The review's findings show that quantitative studies continue to dominate, with experiments, surveys, and structural models being the primary methods. Recent trends indicate a growing interest in non-economic factors like religious values, social norms, perceptions of fairness, and the influence of institutional structures. The studies also found that the interaction between cultural characteristics and institutional quality plays a crucial role in either encouraging or hindering tax compliance. This review confirms that a culture-based approach can enrich the understanding of tax compliance dynamics, especially in developing countries. It recommends that future research should focus more on the qualitative exploration of local cultures, mapping the interaction between cultural values and trust in institutions, and developing culturally based policies to foster voluntary compliance.